Relativistic Proton Levels from Region AR 12673 (GLE #72) and the Heliospheric Current Sheet as a Sun–Earth Magnetic Connection. (13th December 2018) - Augusto, C. R. A.; Navia, C. E.; de Oliveira, M. N.; Nepomuceno, A. A.; Fauth, A. C.; Kopenkin, V.; Sinzi, T.
Abstract: On 2017 September 10 Neutron Monitors (NMs) apparatus located at ground level and high latitudes detected an increase in the counting rate associated to solar energetic particles (SEPs) emission from X8.2-class solar flare and its associated CME. This was the second-highest flare of the current solar cycle. The origin was the active region AR 12673 when it was located at the edge of the west solar disk, magnetically poorly connected with Earth. However, there was a peculiar condition: the solar protons accelerated by the CME shocks were injected within a heliospheric current sheet (HCS) region when Earth was crossing this region. We show that often HCS and SEPs propagation are closely related. If the source locations of SEPs are within or close to HCS, the HCS play the role of a Sun–Earth magnetic connection. SEPs drift around HCS paths, and SEPs are also drift in a wide range of longitudes by the HCSs. In some cases, and especially when Earth crosses the HCS sector, a fraction of these particles can reach Earth with a harder energetic particle flux, triggering a ground-level enhancement (GLE). The blast on 2017 September 10, which triggered the GLE #72, was the second in the current solar cycle. We show that the two GLEs, including all sub-GLEs observed in the current solar cycle, comes from solar explosions that happened within an HCS structure; this behavior is also observed in the GLEs of the previous solar cycle. In general, solar explosions from active regions poorly connected with Earth can trigger GLEs, through the mechanism described above. In all cases, the SEPs drift processes by HCS structures provides an efficient particle transport, allowing the observation of these solar transient events.